سیرت نگاری کے اصول و مبادی: عصری تناظر میں مطالعہ و جائزہ : Principles of Sīrah Writing: A Critical Analysis of Modern Trends - Dr. Rukhsana Shaheen Waraich,Dr. M. Akram Vrik, Sadia Halima (AL-IDRAK JOURNAL, 2022)
The purpose of this study is to determine the key principles of writing the sīrah of Holy Prophet (SAW) as he is the source of light from whom the mankind should take guidance and emulate his exemplary character. The paper has analysed the different trends and styles of codification of the life of the beloved Prophet (SAW) through literature survey of biographies written in different eras. It is argued that unlike the Hadīth and fiqh, biographers of Beloved Prophet (SAW) didn’t deduce and determine the principles of writing biography that resulted in certain discrepancies. The study has proposed a conceptual framework for a comprehensive and effective Prophetic biography based upon the premise that although every era brings different set of challenges and biographers must take them into consideration but there must be determined principles of writing biographies like principles of universality of Prophet (SAW), vitality of the message, goal orientation and practicality in daily life.